2012
DOI: 10.1007/s10457-012-9528-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and diversity of Adansonia digitata L (baobab) in Malawi using microsatellite markers

Abstract: Baobab (Adansonia digitata L) belonging to Bombacaceae family, is one of the most widely used indigenous priority tree species in sub-Saharan Africa, valued in the cosmetic industry for its seed oil, and powdery fruit pulp for juice making. Baobab has high potential for domestication in southern Africa, therefore understanding its genetic diversity and population structuring is warranted. The study investigated the level of genetic diversity and Mantel's test showed a weak positive insignificant correlation (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…Most studies of baobab population structure have focused on microsatellites Larsen & al., 2009;Munthali & al., 2013;Wiehle & al., 2014), plastid DNA (Leong Pock Tsy & al., 2009), or AFLPs ). However, it was previously suggested that A. kilima might be distinct from A. digitata based partly on ITS sequences , leading us to look for evidence of this in a broad sample of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of baobab population structure have focused on microsatellites Larsen & al., 2009;Munthali & al., 2013;Wiehle & al., 2014), plastid DNA (Leong Pock Tsy & al., 2009), or AFLPs ). However, it was previously suggested that A. kilima might be distinct from A. digitata based partly on ITS sequences , leading us to look for evidence of this in a broad sample of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the baobab studies have concentrated on Western and Southern Africa with a strong focus on morphology (Sanchez, 2011; Sanchez et al, 2011b; Mpofu et al, 2012), while genetic studies are rare (Sidibé and Williams, 2002; Assogbadjo et al, 2006; Assogbadjo et al, 2009; Kalinganire et al, 2008; Kyndt et al, 2009). Despite A. digitata 's autotetraploid nature (2 n = 160) and thus challenging data analysis as well as interpretation of results, microsatellite (SSR) markers developed by Larsen et al (2009) were successfully used to differentiate populations and individuals (Munthali et al, 2013). These markers allow for the analysis of the genetic diversity of the species, seed‐ and pollen‐mediated gene flow and inbreeding, and may even help to predict consequences of climatic fluctuations on genetic structures (Larsen et al, 2009).…”
mentioning
confidence: 99%
“…The genetic differentiation was at a low level (G ST = 0.0968) and gene flow (N m = 4.6629) was at a high level among S. davidii populations. Typically, N m > 1 indicates weak differential selection (Rossi et al, 2009;Oja and Talve, 2012;Munthali et al, 2013). Furthermore, the distribution of genetic variation along altitudinal gradients is known to be the result of the interplay of gene flow and genetic drift.…”
Section: Genetic Differentiation Along the Altitudinal Gradientmentioning
confidence: 99%